The Smell of Healthy Choices: Cross-Modal Sensory Compensation Effects of Ambient Scent on Food Purchases - Biswas, Dipayan; Szocs, Courtney (Journal of Marketing Research, 2019)
Managers are using ambient scent as an important strategic element in various service settings, with food-related scents being especially common. This research examines the effects of food-related ambient scents on children’s and adults’ food purchases/choices. The results of a series of experiments, including field studies at a supermarket and at a middle school cafeteria, show that extended exposure (of more than two minutes) to an indulgent food–related ambient scent (e.g., cookie scent) leads to lower purchases of unhealthy foods compared with no ambient scent or a nonindulgent food–related ambient scent (e.g., strawberry scent). The effects seem to be driven by cross-modal sensory compensation, whereby prolonged exposure to an indulgent/rewarding food scent induces pleasure in the reward circuitry, which in turn diminishes the desire for actual consumption of indulgent foods. Notably, the effects reverse with brief (<30 seconds) exposure to the scent. Whereas prior research has examined cross-modal effects, this research adopts the novel approach of examining cross-modal sensory compensation effects, whereby stimuli in one sensory modality (olfactory) can compensate/satisfy the desire related to another sensory modality (gustatory).